2007
DOI: 10.1177/026119290703500410
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Acute Toxicity in HPCT-1E3 Hepatocytoma Cells with Liver-like Transport Activities

Abstract: A battery of in vitro methods has been developed for the prediction of acute oral toxicity, to reduce the number of animals used for this purpose. However, the results of these tests correlate more closely with lethal serum concentrations than with lethal doses. To address this issue, we have further evaluated the HPCT-1E3 model, which may be better able to emulate toxicokinetic factors that occur in vivo, due to the presence in these hepatocytoma cells of endogenous transmembrane carriers and a basal activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 21 publications
4
19
0
Order By: Relevance
“…A test was performed to detect reactive oxygen species and also malondialdehyde as a natural end product of membrane lipid peroxidation. Cell cultures of immortalized rat hepatocytoma cells (HPCT) [51,52] were exposed to OTA and ActD/TNF-α. For control, samples were also analyzed after incubation with H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A test was performed to detect reactive oxygen species and also malondialdehyde as a natural end product of membrane lipid peroxidation. Cell cultures of immortalized rat hepatocytoma cells (HPCT) [51,52] were exposed to OTA and ActD/TNF-α. For control, samples were also analyzed after incubation with H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Because HPCT-1E3 cells are a good model for studying cytotoxicity and express several hepatocyte specific properties in contrast to other immortal cell lines, their suitability as an in vitro model has to be proven in order to replace in vivo experiments [51]. The rat hepatocytoma cell line HPCT-1E3 was maintained in Dulbecco’s modified Eagle’s medium (DMEM) high glucose supplemented with 10% ( v / v ) fetal calf serum, 2 mM L-glutamine, 10 µg/mL insulin, 10 µg/mL inosine, 1.5 µmol/L dexamethasone, 100 IU/mL penicillin and 100 mg/mL streptomycin [53].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in order to test whether HPCT-1E3 cells better reflect the in vivo situation, a preliminary study was performed in our laboratory, by using 20 randomly-selected MEIC substances. HPCT-1E3 IC50 values produced by using the MTT assay showed better correlation with human oral LD50 than with human LC50 values (7). Furthermore, IC50 values obtained from HPCT-1E3 cells correlated better with human LD50 data (r 2 = 0.81; P < 0.001) than did the IC50 values obtained from HepG2 cells (r 2 = 0.55; P = 0.0002).…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, IC50 values obtained from HPCT-1E3 cells correlated better with human LD50 data (r 2 = 0.81; P < 0.001) than did the IC50 values obtained from HepG2 cells (r 2 = 0.55; P = 0.0002). As HepG2 cells lack important liver-specific import transporters, including OATP carriers (8,9), it was suggested that the differences in the predictivity of human toxicity between the two cell lines may Validation of the Hepatocyte-like HPCT-1E3 Cell Line as an In Vitro Model for the Prediction of Acute In Vivo Toxicity Sandra Halwachs, Cathleen Lakoma and Walther Honscha be at least partly due to the carrier-mediated uptake of tested substances in HPCT-1E3 cells (7). However, our previous study revealed variability in the results from a similar test series over a prolonged test period (7), which might be due to a time-dependent alteration of the HPCT-1E3 cell phenotype in long-term culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation